Review of the EVS Curriculum and Textbooks against Emerging Concerns and Contemporary Areas of NEP 2020 - Sharma, Kavita (JOURNAL OF INDIAN EDUCATION, 2023)
To accomplish the aims of education and enable the learners to lead fulfilling lives, different curricular areas evolve as per the societal changes and needs. These are required to be reviewed or revised to accommodate the contemporary changes (both local and global). The recent roll-out of the National Education Policy (NEP) 2020 and National Curriculum Framework for School Education (NCFSE) 2023 in India calls for revision of the curriculum and textbooks in various subjects as sought by the literature, feedback from stakeholders and contemporary developments. This qualitative study analyses how far the contemporary issues, areas, and emerging national and global concerns are addressed in the curriculum and textbooks of Environmental Studies (Classes 3–5) at the national level in India giving useful insights for the ongoing or future curriculum development renewal exercise. The study reveals that the curriculum and textbooks in EVS is age appropriate for children but there is enough scope to address the contemporary issues and concerns.